SPC25 Activates the Warburg Effect to Inhibit Ferroptosis in Prostate Cancer Cells - Mingqiang Su; Jingxian Luo; Wei Chen; Xianyong Li; Dayong Ye; Xiaofu Zeng; Guangqing Fu; Weiwei Xie; Yong Liang (American Journal of Men's Health)
SPC25 is associated with unfavorable outcomes in various cancers, but its role in prostate cancer (PRAD) is unclear. More research is needed on glycolysis and ferroptosis targets in PRAD. Bioinformatics tools were used to analyze SPC25 expression disparities. Gene set enrichment analysis (GSEA) identified pathways enriched by SPC25 and its correlation with glycolytic proteins. SPC25 mRNA transcriptional activity was analyzed by quantitative polymerase chain reaction (qPCR), while protein levels of SPC25, glycolytic markers, and ferroptosis markers were assessed using Western blot. CCK-8 was used to evaluate the effects of SPC25 on cell survival. Ferroptosis levels were measured by flow cytometry and assays for Fe 2+ and malondialdehyde (MDA) content. Glycolytic capacity was assessed using glucose uptake assays, lactate tests, and a Seahorse XF analyzer. In PRAD tissues and cells, SPC25 was notably upregulated and correlated with adverse outcomes. It enhanced cancer cell vitality. GSEA showed SPC25’s strong association with ferroptosis and glycolytic pathways, while Pearson correlation analysis indicated a positive relationship between SPC25 and glycolytic proteins. Overexpression of SPC25 in cell lines noticeably curbed the accumulation of lipid reactive oxygen species, MDA formation, and Fe 2+ content, while it augmented the protein expression of ferroptosis markers. SPC25 stimulated an increase in cellular extracellular acidification rate, glucose uptake, and lactate secretion, while it dampened oxygen consumption rate, and this effect could be counteracted by 2-deoxy- d -glucose (2-DG). Conversely, 2-DG mitigated the ferroptosis indicators that were diminished by SPC25 downregulation, including the reduction of ferroptosis marker protein expression. By upregulating glycolysis in PRAD cells, SPC25 suppresses the occurrence of ferroptosis.